Crosslinking copolymerization of divinylbenzene and maleic anhydride: Morphologies, mechanisms and kinetics - Frank, Randy S. (My University, 2000)
Three distinct copolymer morphologies have been prepared by crosslinking copolymerization of divinylbenzene-55 and maleic anhydride at low monomer concentrations in methyl ethyl ketone 1 heptane mixtures; microspheres, microgels and macrogels. These morphologies depended primarily upon solvent composition and changed from microspheres and microgels to macrogels with increasing methyl ethyl ketone volume fractions. The effect of solvent composition, crosslinker concentration and monomer loading on the observed morphologies were investigated using electron microscopy, viscosity, and light scattering experiments. Microgels were found to be precursors to both macrogels and microspheres and mechanisms for the formation of each morphology are proposed. Copolymerization ofdivinylbenzene-55 and maleic anhydride occurs at higher rates than homopolymerization of divinylbenzene-55. This affects several aspects of the precipitation polymerization leading to polydisperse nuclei and diffusion-controlled particle growth. The divinyl components ofdivinylbenzene-55 were shown to exhibit increased reactivity over the ethylvinyl species: This different reactivity results in a crosslink gradient in DVB-55/MAn microspheres and variable crosslinking in microgels depending on what stage ofthe reaction they are formed in.
Keywords: Chemistry; Chemistry